Differential Inhibitory Effects of Curcumin Between HPV+ve and HPV–ve Oral Cancer Stem Cells - Bano, Nasreen; Yadav, Manisha; Das, Bhudev C. (Frontiers in Oncology, 2018)
Abstract Aim: To investigate the role of a herbal antioxidative compound curcumin on cell proliferation, orosphere formation and miRNA-21 expression in HPV16+ve/-ve oral cancer stem cells. Materials and methods: Oral cancer stem cells were isolated from HPV+ve/HPV-ve oral cancer cell lines by FACS and stemness markers. MTT, spheroid assay and qRT-PCR were employed to examine the effects of curcumin. Results: Curcumin treatment in micromolar concentration (0-50 µM) demonstrated significant differential inhibition in CSC proliferation, orosphere formation and miRNA-21 expression in a dose dependent manner, the effect being highly pronounced in HPV positive CSCs. Conclusion: The strong and dose-dependent inhibitory effects of curcumin on cell proliferation, stemness and miRNA appear to be due to its chemosensitizing and anticancer effects on OSCC-CSCs. Keywords: Cancer Stem Cells (CSCs), Oral squamous cell carcinoma (OSCC), curcumin, human papillomavirus (HPV), SP cells (side population), micro-RNA (miRNA)